Structural insight into [Fe–S2–Mo] motif in electrochemical reduction of N2 over Fe1-supported molecular MoS2. Issue 2 (12th November 2020) - Zheng, Jianwei; Wu, Simson; Lu, Lilin; Huang, Chen; Ho, Ping-Luen; Kirkland, Angus; Sudmeier, Tim; Arrigo, Rosa; Gianolio, Diego; Edman Tsang, Shik Chi
Abstract : A nitrogenase-inspired inorganic-based chalcogenide system containing [Fe–S2 –Mo] motif is developed for the efficient electrochemical conversion of N2 to NH3 . Abstract : The catalytic synthesis of NH3 from the thermodynamically challenging N2 reduction reaction under mild conditions is currently a significant problem for scientists. Accordingly, herein, we report the development of a nitrogenase-inspired inorganic-based chalcogenide system for the efficient electrochemical conversion of N2 to NH3, which is comprised of the basic structure of [Fe–S2 –Mo]. This material showed high activity of 8.7 mgNH3 mgFe −1 h −1 (24 μgNH3 cm −2 h −1 ) with an excellent faradaic efficiency of 27% for the conversion of N2 to NH3 in aqueous medium. It was demonstrated that the Fe1 single atom on [Fe–S2 –Mo] under the optimal negative potential favors the reduction of N2 to NH3 over the competitive proton reduction to H2 . Operando X-ray absorption and simulations combined with theoretical DFT calculations provided the first and important insights on the particular electron-mediating and catalytic roles of the [Fe–S2 –Mo] motifs and Fe1, respectively, on this two-dimensional (2D) molecular layer slab.